Measurement of the 3D geometry of the fascial arches in women with a unilateral levator defect and “architectural distortion” - LARSON, Kindra A. (2011)
OBJECTIVE: The arcus tendineus fascia pelvis (ATFP) and arcus tendineus levator ani (ATLA) are elements of anterior vaginal support. This study describes their geometry in women with unilateral levator ani muscle defects and associated “architectural distortion.” STUDY DESIGN: Fourteen subjects with unilateral defects underwent MRI. 3-D models of the arcus were generated. Locations of these relative to an ilial reference line were compared between unaffected and affected sides. RESULTS: Pronounced changes occurred on the defect sides’ ventral region. The furthest point of the ATLA lay up to a mean 10.2mm (p=0.01) more inferior and 6.5mm (p=0.02) more medial than that on the intact side. Similarly, the ATFP lay 6 mm (p=0.01*) more inferior than on the unaffected side. CONCLUSION: The ventral arcus anatomy is significantly altered in the presence of levator defects and architectural distortion. Alterations of these key fixation points will change supportive force direction along the lateral anterior vaginal wall, increasing the risk for anterior vaginal wall prolapse.